2010
DOI: 10.1371/journal.pone.0011811
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dengue Virus Type 2: New Insights on the 2010 Brazilian Epidemic

Abstract: Dengue viruses (DENV) serotypes 1, 2, and 3 have been causing yearly outbreaks in Brazil. In this study, we report the re-introduction of DENV2 in the coast of São Paulo State. Partial envelope viral genes were sequenced from eighteen patients with dengue fever during the 2010 epidemic. Phylogenetic analysis showed this strain belongs to the American/Asian genotype and was closely related to the virus that circulated in Rio de Janeiro in 2007 and 2008. The phylogeny also showed no clustering by clinical presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
32
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 28 publications
12
32
0
3
Order By: Relevance
“…An analysis of the envelope (E) gene of isolates from Rio de Janeiro and São Paulo collected during 2007–2008 and 2010 revealed that at least two lineages of the American-Asian genotype of DENV-2 have circulated in Brazil [20]–[22]. In addition, the virus that circulated in São Paulo in 2010 was closely related to the virus that circulated in Rio de Janeiro in 2007 and 2008 [21].…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the envelope (E) gene of isolates from Rio de Janeiro and São Paulo collected during 2007–2008 and 2010 revealed that at least two lineages of the American-Asian genotype of DENV-2 have circulated in Brazil [20]–[22]. In addition, the virus that circulated in São Paulo in 2010 was closely related to the virus that circulated in Rio de Janeiro in 2007 and 2008 [21].…”
Section: Introductionmentioning
confidence: 99%
“…American/Asian genotype DENV-2 strains isolated during a São Paulo state outbreak (2010) were closely related to strains circulating during the 2007–8 epidemic in Rio de Janeiro and Ribeirão Preto, but distinct from those of earlier DENV-2 epidemics in Brazil. No phylogenetic clustering by clinical presentation was observed [35]. …”
Section: Resultsmentioning
confidence: 99%
“…Our study reports that the Panamanian DENV-2 strain, circulating during 2011 outbreak, belongs to Asian/American genotype (AS/AM). The introduction of this genotype has been linked with outbreaks with high mortality rates 41,45,46 in Peru 47 , Nicaragua 27 and Brasil 48 . Our phylogenetic analysis clustered Panama 2011 DENV-2 strains in clade 2 sub-clade 2b.I using previous classification of DENV-2 AS/AM circulating in Central America 26 , closely related with strains from Mexico 2011 and Guatemala 2009.…”
Section: Discussionmentioning
confidence: 99%